Ibn Sina's Idea of Nature and Change - Arif, Syamsuddin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2007)
This article discusses Ibn Sina's idea of 'nature' and his theory of change, including that of substantial change, in comparison with the views held by Aristotle and some Pre-socratic philosophers.